The oral cavity in leprosy: what clinicians need to know. (3rd October 2016) - Rodrigues, GA; Qualio, NP; de Macedo, LD; Innocentini, LMAR; Ribeiro‐Silva, A; Foss, NT; Frade, MAC; Motta, ACF
Abstract : Leprosy is a chronic infectious disease caused by Mycobacterium leprae, a bacillus that has a tropism for skin and peripheral nerves. Leprosy treatment is based on a multidrug therapy established by the World Health Organization in 1982 and, despite its widespread use, Brazil ranks second worldwide in numbers of cases. Oral involvement in leprosy has been poorly described in the literature, and few studies have shown that although the bacillus is found in mucosa, specific leprosy lesions are rare and affect patients with advanced stages of the disease. This review aimed to assess the literature on oral manifestations in leprosy and the aspects involving oral cavity in leprosy pathogenesis.